"But it doesn't come naturally": how effort expenditure shapes the benefit of growth mindset on women's sense of intellectual belonging in computing. Issue 3 (2nd October 2017) - Stout, Jane G.; Blaney, Jennifer M.
Abstract: Research suggests growth mindset, or the belief that knowledge is acquired through effort, may enhance women's sense of belonging in male-dominated disciplines, like computing. However, other research indicates women who spend a great deal of time and energy in technical fields experience a low sense of belonging. The current study assessed the benefits of a growth mindset on women's (and men's) sense of intellectual belonging in computing, accounting for the amount of time and effort dedicated to academics. We define "intellectual belonging" as the sense that one is believed to be a competent member of the community. Whereas a stronger growth mindset was associated with stronger intellectual belonging for men, a growth mindset only boosted women's intellectual belonging when they did not work hard on academics. Our findings suggest, paradoxically, women may not benefit from a growth mindset in computing when they exert a lot of effort.